Environmental Education in Forming Attitudes ofEnvironmental Care for Students - Istiqomah, Istiqomah; Suwondo, Suwondo; L.N Firdaus, L.N Firdaus (Journal of Educational Sciences, 2020)
Current environmental problems have become a serious threat to human life. One way to reduce this threat is to change the  paradigm  of  the  younger  generation  through education. Environmental Education (PLH) is the right step to implement, especially in Adiwiyata schools. This study aims to analyze students environmental care attitudes by learning  monolithic  and  integrated  environmental education. This research was conducted in 4 adiwiyata high schools. The method used is a survey. The total sample was307 students. The technique used through the questionnaire environmental attitudes of students. Data analysis was performed by t-test. The t-test results showed that therewere differences in students' environmental care attitudes between monolithic learning and integration. Differences in attitudes to care for the environment are found in 3 indicators namely, attitudes towards energy, attitudes towards flora and fauna and attitudes towards the social and human environment. Analysis of environmental care attitudes category found that monolithic PLH learning was1.24%  in  the  excellent  category,  98.76  in  the  goodcategory.  While  PLH  integration  is  1.39%  very  good,93.10% is good and 5.51% is low. It was concluded that students with monolithic PLH learning had environmental care attitudes that were better than students' attitudes withPLH integration learning.